If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43 + 16c + -18d + 56c + 16d = 0 Reorder the terms: 43 + 16c + 56c + -18d + 16d = 0 Combine like terms: 16c + 56c = 72c 43 + 72c + -18d + 16d = 0 Combine like terms: -18d + 16d = -2d 43 + 72c + -2d = 0 Solving 43 + 72c + -2d = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-43' to each side of the equation. 43 + 72c + -43 + -2d = 0 + -43 Reorder the terms: 43 + -43 + 72c + -2d = 0 + -43 Combine like terms: 43 + -43 = 0 0 + 72c + -2d = 0 + -43 72c + -2d = 0 + -43 Combine like terms: 0 + -43 = -43 72c + -2d = -43 Add '2d' to each side of the equation. 72c + -2d + 2d = -43 + 2d Combine like terms: -2d + 2d = 0 72c + 0 = -43 + 2d 72c = -43 + 2d Divide each side by '72'. c = -0.5972222222 + 0.02777777778d Simplifying c = -0.5972222222 + 0.02777777778d
| y-9.68=-4.5 | | 94=60+2x | | 6x+-10=32 | | 0.24x=18.26 | | 100=2x+3+51 | | 5x+7=-19-8x | | 2n+6(n-7)= | | 5x-4=-119 | | 8+3[5+2(12-8)-1]= | | 9y-36x=90 | | 3x+33=5x-9 | | y+2y+3z= | | 12x-7=137 | | 163-4x=41x+23 | | 4x=x-11 | | 14-8x=44-22x | | 5x+12=-114-9x | | 5x+12=-144-9x | | 97-4x=2x+7 | | 4n-40=7(2n+2) | | 84-4x=7x+18 | | 9+12x=53+x | | 71-5x=7x+23 | | t^3-2t^2-9t+18=0 | | -9+x=12 | | -59-10x=10x+21 | | 6x+9=-126-9x | | -24-3x=12-9x | | 12(2x-3)=6x | | 9x-28=80 | | 7x-12=23 | | 4x+27=11x-29 |